Accuracy of digital impressions for three-unit and four-unit implant supported fixed dental prostheses using a novel device - Tzu-Yung Kao; Min-Chieh Hsieh; Chi-Pin Hsu; Chi-Chun Liao; Chih-Ling Chang (Elsevier, 2023)
Background/ purpose: Accuracy of digital implant impressions was considered questionable due to the lack of anatomical reference points between implants and the similarities in scan body morphology, which lead to the purpose of this research is to propose a simple and convenient technique to improve the accuracy of scanning. Materials and methods: Four implant analogues (teeth: 15, 17, 24, and 27) were inserted into a stone model of a partially edentulous maxilla; two implants were inserted on each side, creating a three-unit span and a four-unit span. The model was scanned using a 3Shape E4 dental laboratory scanner for reference and a TRIOS 3 intraoral scanner for testing. Each side was scanned 10 times, both with and without the novel device attached to the scan bodies. The trueness and precision of interimplant distances (linear deviations), and interimplant angulations (angle deviations) between the scan bodies were determined using software. A Mann-Whitney U test was used to determine statistical differences between subgroups. Results: Significant differences were discovered in the trueness of angular deviations (−0.20° ± 0.15° vs. −0.01° ± 0.11º) and precision of linear deviations (11.14 ± 6.35 vs. 3.10 ± 2.14 μm) for the four-unit groups. Conclusion: The novel device significantly improved scanning accuracy for a four-unit groups (approximately 22.93 mm) compared to three-unit groups.